The Concept of Indicators from Islamic Perspective - Ismail , Nor Hanani (International Journal of Psychosocial Rehabilitation, 2019)
This paper has two main objectives. The first objective identifies the concept of the indicators that are constructed based on the al-Quran and al-Sunnah. The second objective analyses the scholars’ views on the selected divine proofs that contain the concept of indicators. Generally, indicators refer to the measurements or characteristics to measure a change or an exchange. Hence, indicators become an important tool in providing results and decisions. If the measurement is wrong, then the findings from the measurement are inaccurate. Indicators that are constructed based on Western resources and worldview will produced findings that are in line with the Western worldview. If the same condition is used to measure Islamic elements or the affairs of the Muslims, the findings obtained will certainly do not reflect the Islamic worldview. As such, in matters relating to Islam and the affairs of the Muslims there is a need for the concept of indicators to be in accordance with the Islamic perspective so that validity or truth can be attained as a result of such measurement. The question is what is the concept of indicators based on the Islamic perspective and what are the elements contained in the concept of indicators? Both of these issues are examined based on the interpretations of the scholars on the concept of the indicators based on the al-Qur’an and al-Sunnah. Therefore, this paper aims to address both these issues through textual analysis of selected literatures. For the first issue, this paper identifies the concept of indicators contained in al-Qur’an and al-Sunnah. For the second question, this paper discusses the views of scholars and subsequently formulates the elements for the concept of indicators from the Islamic perspective.